Challenges to increasing the soil carbon pool of agro-ecosystems in China - Er-da LIN; Li-ping GUO; Hui JU (Journal of Integrative Agriculture, 2018)
Climate change will place agro-ecological systems and food security at serious risk. At the 21st Conference of the Parties (COP21) in Paris in December of 2015, parties to the United Nations Framework Convention on Climate Change (UNFCCC) reached a historic agreement (Paris Agreement) to combat climate change and to accelerate and intensify the actions and investments needed for a sustainable low carbon future. An initiative named the “4‰ initiative: Soils for food security and climate” was proposed by the French Minister of Agriculture, and this initiative was launched officially at the COP21 and adopted by many global organizations. The aim of this initiative was to increase carbon sequestration in soil to mitigate fossil fuel combustion emissions of greenhouse gasses. The present study found that China has high CO2 emissions but a low soil carbon pool, and indicates that 4‰ increments of the soil carbon pool will not be sufficient to offset national CO2 emissions. The current soil carbon sequestration rate would also not reach the mean level requested by the initiative. Therefore, China faces big challenges to achieve this initiative. An integrated use of straw technology may be used more widely to improve carbon sequestration, and other opportunities include improved fertilizer use efficiency and greenhouse gas mitigation through the waste management project under construction in China. This paper suggests that China may put forward the biomass treatment centered high yield and fertilizer-carbon sequestration project to enhance resilience of agro-ecosystems to climate change.